Art Interventions as Community Art:The dilemma of continuity in the case of the Enontekiö Art Path - Härkönen, Elina (2019)
In this article the principles of cultural sustainability and the role of continuity are discussed in art interventions as a form of community art. The case of art-based action research is the Enontekiö Art Path project that took place in northern Finland 2016-2017. The project was a collaboration initiative between the municipality of Enontekiö and the Department of Art Education, University of Lapland and it aimed to increase access of art for people living outside the municipality centre. During the project, university students organised six art interventions in different villages of Enontekiö. The continuity happened between the workshop through constant evaluation of the actions and gradually increased also the engagement of the people involved in the project.